Типология понятийно-категориального аппарата феноменологической социологии - Шульга, А. (Социология: теория, методы, маркетинг, 2007)
The article deals with theoretical problems of phenomenological sociology. The author analyses Husserl's conception as a philosophical basis of the phenomenological sociology paradigm. The analysis is intended for elaboration of the typology of conceptual apparatus within the framework of phenomenological sociology.